Vitamin D deficiency influences fatty acid metabolism. (January 2019) - Nandi, A.; Wadhwani, N.; Joshi, S.R.
Highlights: Vitamin D deficiency influences reproductive performance. Its deficiency alters rat liver, plasma and erythrocyte fatty acid composition and metabolism. Vitamin D deficiency in rat alters mRNA levels of fatty acid desaturases as well as fatty acid desaturase activity index. Abstract: Reports indicate that maternal vitamin D deficiency may be associated with increased inflammation. Long chain polyunsaturated fatty acids (LCPUFAs); omega-3 and omega-6 fatty acids are known to have anti-inflammatory and pro-inflammatory properties respectively. The present study examines the effect of vitamin D deficiency on fatty acid composition and metabolism in a rat model. Female Wistar rats were randomly divided into two groups ( n  = 8/group) as follows; control and vitamin D deficient (VDD). Diets (control: 1000 IU D3/kg diet; VDD: 0 IU D3/kg diet) were given from weaning and continued throughout pregnancy. Pregnant female rats were dissected on gestational day 20 to collect blood, liver and placenta. The VDD diet reduced maternal serum 25-hydroxyviatmin D3 levels ( p  < 0.001) as compared to control. Maternal vitamin D deficiency resulted in lower total weight gain and placental weight ( p  < 0.05 for both) during pregnancy. Animals from VDD group demonstrated higher arachidonic acid (AA) levels in both the liver and plasma ( p  < 0.05 for both) as compared to control. Liver, plasma and placental monounsaturated fatty acid levels (MUFA) were lower ( p  < 0.01 for all) while plasma total saturated fatty acids (SFA) ( p  = 0.05) were higher in the VDD group. Animals from the VDD group demonstrated lower ∆9-desaturase activity index ( p  < 0.01 for all) in the liver, plasma and placenta. The plasma ∆5-desaturase activity index ( p  < 0.05) was higher although no change was observed in the ∆6-desaturase activity index. However, the mRNA levels of liver ∆6-desaturase was lower ( p  < 0.05) in the VDD group. Our findings indicate that maternal vitamin D deficiency influences fatty acid desaturase activity and expression and therefore alters maternal fatty acid metabolism. Graphical abstract: